Isocitrate Dehydrogenase Mutations in Glioma: From Basic Discovery to Therapeutics Development - Huang, Juan; Yu, Jialong; Tu, Lin; Huang, Nanqu; Li, Hang; Luo, Yong (Frontiers in Oncology, 2019)
Isocitrate dehydrogenase (IDH) is a key rate-limiting enzyme in the Krebs cycle that plays an important role in energy metabolism. In recent years, it has been found that IDH mutations are closely related to the occurrence and development of glioma, and it is a notable potential therapeutic target. First, IDH mutations can produce high levels of 2-hydroxyglutaric acid (2-HG), thereby inhibiting glioma stem cell differentiation. At the same time, IDH mutations can upregulate vascular endothelial growth factor (VEGF) to promote the formation of the tumour microenvironment. In addition, IDH mutations can also induce high levels of hypoxia-inducible factor-1α (HIF-1α) to promote glioma invasion. Ultimately, these changes will lead to the development of glioma. Currently, a large number of IDH inhibitors and vaccines have entered clinical trials, representing progress in the treatment of glioma patients.